TEACHING SPEAKING THROUGH A PRAGMATIC APPROACH IN ISLAMIC STATE SENIOR HIGH SCHOOL - Isnaini, Nur Alfiana; Pramudiharjo, Fendi Sebastian (Jurnal Pendidikan Humaniora, 2024)
This study examines teachers' perspectives on the effectiveness of the pragmatic approach in teaching speaking skills in public senior secondary schools under the Merdeka Curriculum. The research investigates the alignment of speaking materials with the curriculum and identifies challenges faced by teachers in implementing this approach. Employing a qualitative case study methodology, the study utilized observations, document analyses, and teacher interviews. The findings reveal that teachers effectively integrated external resources, social media, and classroom activities—such as role-plays and dialogues—to enhance student engagement and learning outcomes. A holistic assessment approach was employed, emphasizing contextually appropriate expressions in accordance with the curriculum's focus on communicative competence. Despite challenges such as limited time, teachers innovatively addressed these issues through techniques like video recordings and social media-based assessments. The results demonstrate the pragmatic approach's effectiveness and adaptability in equipping students with real-world communication skills. This study contributes to the understanding of the pragmatic approach's application within the Merdeka Curriculum, offering valuable insights for advancing language education in Madrasah Aliyah and similar contexts.